Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13006-020-00345-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding support at an Australian Breastfeeding Association drop-in service: a descriptive survey

Abstract: Background In Australia, during the early establishment phase of breastfeeding, women can access telephone peer support counselling provided by the Australian Breastfeeding Association (ABA) however options for face-to-face peer support are limited. The known factors which improve ongoing and exclusive breastfeeding include face-to-face support, peer and/or professional support, and trained personnel. This study aimed to examine women’s experiences of accessing one breastfeeding drop-in peer su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
2
5
0
8
Order By: Relevance
“…Our themes and global theme are similar to a number of other studies, and support theoretical perspectives described by Lakey and Cohen [ 30 ]. The global theme is consistent with other studies that have reported the importance of non-judgemental, empathetic support [ 35 , 36 ]. The social connection with their peers, is described by mothers as helping them to feel less alone [ 27 ] and isolated [ 37 ], as a friendship, someone close [ 38 ] and at times a confidante.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our themes and global theme are similar to a number of other studies, and support theoretical perspectives described by Lakey and Cohen [ 30 ]. The global theme is consistent with other studies that have reported the importance of non-judgemental, empathetic support [ 35 , 36 ]. The social connection with their peers, is described by mothers as helping them to feel less alone [ 27 ] and isolated [ 37 ], as a friendship, someone close [ 38 ] and at times a confidante.…”
Section: Discussionsupporting
confidence: 90%
“…This connection better enabled participants to be relaxed, frank and open in their conversations, with the relationship providing positive effects from companionship and intimacy [ 30 ]. The peer was described as non-judgemental [ 35 , 39 ] empathetic and understanding, attributes which allowed for low-social conflict within the relationship. Participants felt they were able to better cope and manage the stressors [ 40 ] of breastfeeding and parenting, through the peer sharing their own stories, normalising the mother’s experience [ 28 , 40 , 41 ] and helping them to understand their struggles were not unique, supporting the mother’s self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the subjects needed by mothers during the provision of accompaniment were exclusive breastfeeding, correct breastfeeding techniques and positions, breastfeeding problems and how to overcome them, and breastfeeding preparation for working mothers. These findings were also aligned with a previous study, where it was found that the lack of skills regarding the correct breastfeeding position and proper placement while breastfeeding [24] and the preparation of breastfeeding for working mothers become obstacles to the success of exclusive breastfeeding [25]. In addition, mothers with a high level of breastfeeding knowledge with a high score had a greater potential to give exclusive breastfeeding for six months [26].…”
Section: Discussionsupporting
confidence: 89%
“…Support is a practice that reduces the abandonment of breastfeeding [ 48 , 49 ]. In the literature, the organization of home support is described as an attempt to regain as many women as possible to the practice of exclusive breastfeeding, at least for the first few months [ 50 ].…”
Section: Discussionmentioning
confidence: 99%